Deletion of MAP2K2/MEK2: a novel mechanism for a RASopathy?. (2nd April 2013) - Nowaczyk, M.J.M.; Thompson, B.A.; Zeesman, S.; Moog, U.; Sanchez‐Lara, P.A.; Magoulas, P.L.; Falk, R.E.; Hoover‐Fong, J.E.; Batista, D.A.S.; Amudhavalli, S.M.; White, S.M.; Graham, G.E.; et al.
<x xml:space="preserve">Abstract</x> RASopathies are a class of genetic syndromes caused by germline mutations in genes encoding Ras/mitogen‐activated protein kinase (Ras/MAPK) pathway components. Cardio‐facio‐cutaneous (CFC) syndrome is a RASopathy characterized by distinctive craniofacial features, skin and hair abnormalities, and congenital heart defects caused by activating mutations of BRAF, MEK1, MEK2, and KRAS. We define the phenotype of seven patients with de novo deletions of chromosome 19p13.3 including MEK2; they present with a distinct phenotype but have overlapping features with CFC syndrome. Phenotypic features of all seven patients include tall forehead, thick nasal tip, underdeveloped cheekbones, long midface, sinuous upper vermilion border, tall chin, angular jaw, and facial asymmetry. Patients also have developmental delay, hypotonia, heart abnormalities, failure to thrive, obstructive sleep apnea, gastroesophageal reflux and integument abnormalities. Analysis of epidermal growth factor‐stimulated fibroblasts revealed that P‐MEK1/2 was ∼50% less abundant in cells carrying the MEK2 deletion compared to the control. Significant differences in total MEK2 and Sprouty1 abundance were also observed. Our cohort of seven individuals with MEK2 deletions has overlapping features associated with RASopathies. This is the first report suggesting that, in addition to activating mutations, MEK2 haploinsufficiency can lead to dysregulation of the MAPK pathway.